2009
DOI: 10.1007/s00701-009-0517-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of early secondary complications in patients with spontaneous subarachnoid hemorrhage based on accelerated sympathovagal ratios

Abstract: This study confirmed that during early SAH period, patients with and without complications presented different patterns of sympathovagal changes. LF/HF slope during the first 3 days was a significant predictor of secondary complications after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…After full article review, 22 studies met the inclusion criteria (http://onlinelibrary.wiley.com/doi/10.1111/ijs.12573/suppinfo) . Ten studies examined HRV and 11 reported on BRS in acute stroke patients. One study examined both parameters .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After full article review, 22 studies met the inclusion criteria (http://onlinelibrary.wiley.com/doi/10.1111/ijs.12573/suppinfo) . Ten studies examined HRV and 11 reported on BRS in acute stroke patients. One study examined both parameters .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies included patients with ischemic stroke only (7,11,12,16,21,23,24,26,27,31,32,34,35); five of them focused on middle cerebral artery (MCA) strokes (7,16,21,34,35). Three studies exclusively examined patients with intracerebral hemorrhages (10,28,33) and one study focused on subarachnoid hemorrhages (30). Five studies included multiple stroke subtypes (8,20,22,25,29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympathetic over-activation has been identified in patients with subarachnoid hemorrhage [18] and is associated with neurogenic cardiomyopathy [19] and other complications [20]. In patients with acute cerebral infarction, increased serum norepinephrine levels have been associated with poor outcome at one year [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether similar mechanisms are at play in seizures following brain injury in humans, as baseline metabolism is altered, waves of spreading depolarization, spreading ischemia, and spreading convulsions are frequent, and vasoreactivity is frequently abnormal . Furthermore, impairment of the autonomic nervous system, including tachycardia and tachypnea, are common after acute brain injury, which may impair typically observed compensatory responses for seizures such as those seen in epilepsy patients…”
mentioning
confidence: 99%